Play fighting revisited: its design features and how they shape our understanding of its mechanisms and functions - Pellis, Sergio M.; Pellis, Vivien C.; Ham, Jackson R. (Frontiers in Ethology, 2024)
Play fighting has been one of the most intensely studied forms of play and so has provided some of our deepest insights into the understanding of play in general. As the label implies, this behavior resembles serious fighting, in that the animals compete for an advantage over one another, but unlike true aggression, for play fighting to remain playful, it also incorporates a degree of cooperation and reciprocity -restrained competition seems to be its hallmark. Despite these common features, it should be noted that both the advantage competed over and the mechanisms by which restraint is achieved varies across species. Such variation mitigates simple generalities. For example, how empirical support for a proposed adaptive function in one species not being replicated in another, is to be interpreted. What has emerged over the past few decades is that play fighting is diverse, varying across several dimensions, some superficial, some fundamental, making choosing species to compare a challenge. In this paper, we explore various design features that constitute play fighting and the ways these can be modified across different species and lineages of species. Given that a major pillar of ethology is that description precedes explanation, having a good grasp of the behavioral diversity of play fighting is an essential starting point for detailed analyses of the mechanisms and functions of play. We show that commonalities across species likely involve different mechanisms than do species idiosyncrasies, and that different styles of play fighting likely afford different adaptive opportunities.